An Error Analysis Of Article System: A Case Of ESP Students - Maya Ulyani (Jurnal Yudistira : Publikasi Riset Ilmu Pendidikan dan Bahasa, 2024)
Analyzing errors is very important for ESP students because they can relate to their work, it also provides ESP students with corrections Errors in learning behavior. This research aimed to investigate the errors, the most prominent type, and the causes of errors in using English articles in academic writing. The Researcher examined the academic writing by the ESP students. The researchers use an analytical parameter developed based on Biber et al. (1999) to analyze article errors. The causes of errors were obtained through a questionnaire developed based on the categories proposed by Brown (2007). After analyzing the data, the Researcher found 30 errors in Addition, Omission, and substitution categories. The most prominent type of Error is omission error, with a frequency of 293 occurrences or 76%. The main type of omission error is an omission of the definite article "the" before nouns or noun phrases. In contrast, the major cause of errors is mother tongue influence, with an average mean of 4.17 in the questionnaire responses. This study's findings indicate the need for teaching strategies and materials to prevent common article usage errors.